INVESTIGATING LEXICAL DIVERSITY OF ONLINE ENGLISH NEWSPAPER EDITORIALS ACROSS COUNTRIES - Indarti, Dwi (Study Program of English Literature, 2019)
Online media or digital media is an internet based communication technology to share and to exchange the latest information throughout the world. This study aims to investigate the lexical diversity of editorials section published in English online media from across ten countries; Egypt, UK, Indonesia, Japan, Malaysia, Russia, USA, Pakistan, Singapore and Nigeria. By using a batch mode of web-based interface to the lexical calculation proposed by Laufer and Nation (1995), namely Second Language Lexical Frequency Profile (L2LFP), this paper focused on the production of tokens, types, type-token ratio (TTR) and academic words of ten online English newspaper editorials from two native English countries and eight non-native English countries. The results show that an editorial published in The Today Online newspaper from Singapore consists the highest score of tokens (987), types (431) and academic words (52), but the least score of TTR (0.44). Nevertheless, the highest score of TTR is not produced by The Today Online. The highest score of TTR (0.60) is gained by The Pakistan Today, even though The Pakistan Today only consists 273 tokens, 223 types and 38 academic words. Despite of Laufer and Nation’s (1995) argumentation that native writer has higher TTR’s score than non-native writer, this paper showed different results. The native online newspaper: The Guardian from U.K and The New York Times from USA has TTR’s score of 0.48 and 0.47. Meanwhile, most of non-native online newspapers has higher TTR’s scores.